Damage reduction of Acromyrmex lobicornis in Pinus ponderosa using mixed pine species in combination with push–pull tools - Alma, Andrea Marina (2023)
Leaf-cutting ants (LCAs) cause significant damage to forest plantations and are mainly managed by broad-spectrum synthetic insecticides. In Patagonia, Pinus ponderosa (Pinales: Pinaceae) (Douglas 1836) and Pinus contorta (Pinales: Pinaceae) (Dluglas 1838) are the predominant pine species in forest plantations. Previous research has shown that dehydrated citrus pulp is an LCAs attractant, and tea tree essential oil acts as an LCAs repellent. We evaluated the use of dehydrated citrus pulp and tea tree oil to manage LCAs behaviour in a push–pull setting, using mixed pine species in small plot fields, to reduce the LCA Acromyrmex lobicornis (Hymenoptera: Formicidae) (Emery, 1888) damage in young P. ponderosa plants. We combined the treatment with attractant and repellent in a mono-specific plantation design (three ponderosa plants surrounded with pulp and three sprayed with tea tree extract) or mixed plantation designs (three contorta plants with pulp and three ponderosa plants with tea tree). The combination of both mono-specific and mixed plantations with push–pull stimuli delayed discovery and decreased the damage in pines sprayed with the repellent. Mono-specific as well as mixed species designs were equally effective, reducing ant damage and increasing ~50% the survival probability of P. ponderosa when push–pull stimuli were applied. The use of a push–pull strategy with plant-based compounds provides potential as a management tool that reduces and delays LCA damage in pine trees.